The young stellar population of the metal-poor galaxy NGC 6822. Issue 1 (19th September 2019) - Jones, Olivia C; Sharp, Michael J; Reiter, Megan; Hirschauer, Alec S; Meixner, M; Srinivasan, Sundar
ABSTRACT: We present a comprehensive study of massive young stellar objects (YSOs) in the metal-poor galaxy NGC 6822 using IRAC and MIPS data obtained from the Spitzer Space Telescope . We find over 500 new YSO candidates in seven massive star formation regions; these sources were selected using six colour–magnitude cuts. Via spectral energy distribution fitting to the data with YSO radiative transfer models we refine this list, identifying 105 high-confidence and 88 medium-confidence YSO candidates. For these sources, we constrain their evolutionary state and estimate their physical properties. The majority of our YSO candidates are massive protostars with an accreting envelope in the initial stages of formation. We fit the mass distribution of the Stage I YSOs with a Kroupa initial mass function and determine a global star formation rate of 0.039 M_ yr^-1 . This is higher than star formation rate estimates based on integrated UV fluxes. The new YSO candidates are preferentially located in clusters which correspond to seven active high-mass star-formation regions which are strongly correlated with the 8 and 24 μm emission from PAHs and warm dust. This analysis reveals an embedded high-mass star formation region, Spitzer I, which hosts the highest number of massive YSO candidates in NGC 6822. The properties of Spitzer I suggest it is younger and more active than the other prominent H ii and star-formation regions in the galaxy.